2019
DOI: 10.18203/2320-6012.ijrms20191650
|View full text |Cite
|
Sign up to set email alerts
|

Y-chromosomal STR variation in Kurds and Arabs population in Iraqi Kurdistan

Abstract: Background: The Iraqi Kurdistan local population involves more than eight gatherings of tenants. The Muslim Kurds make up most of the population and after that the Yezidi Kurds. Alternate gatherings incorporate Armenians, Assyrian, Chaldea, Syriacs, and little minority of Arab and Turkmen individuals.Methods: A total of 36 unrelated males from the two population groups in Iraqi Kurdistan: Kurds and Arabs were analyzed for eight Y-chromosome STRs (DYS19, DYS392, DYS437, DYS448, DYS456, DYS458, DYS635 and Y-GATA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
1
1
2
Order By: Relevance
“…All these primers that are used during this study can be considered informative due to its high values. The studies' outcomes are in agreement with results that have been done byFattah et al, (2019) they were reported high values of PIC. Furthermore,Naji (2020) found that DYS19 and DYS393 primers were the most polymorphic in comparing to other primers.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…All these primers that are used during this study can be considered informative due to its high values. The studies' outcomes are in agreement with results that have been done byFattah et al, (2019) they were reported high values of PIC. Furthermore,Naji (2020) found that DYS19 and DYS393 primers were the most polymorphic in comparing to other primers.…”
supporting
confidence: 91%
“…High number of allele per each population suggests a high amounts of genetic diversity in that population. Fattah et al (2019) reported that the average number of alleles in Behdinan population was 5.125, whereas in this study the number of alleles in Behdinan population (7.8) was much higher, this may be due to use larger number of markers. The allele frequency in these three populations were not the same with each other.…”
Section: )contrasting
confidence: 63%
“…High number of alleles per each population suggests high amount of genetic diversity in the population. Fattah et al (2019) reported that the average number of alleles in Kurd population was 5.125, while in this study the number of alleles in Kurd population (10.91) was much higher, this may be due to the use of larger number and different primers. High number of alleles within each population indicates a great level of genetic diversity.…”
Section: Discussioncontrasting
confidence: 54%
“…The current study, the first to our knowledge, focuses on one group of the Kurdish population (Sorani Kurds) in Iraq, separated from the Kurmanji Kurdish group in the northwest of Iraq on the border with Turkey. In addition, a higher number of population samples were collected than in the previous paternal lineage studies of the Kurdish population [ 19 , 20 , 47 ], which is also an important consideration in obtaining more reliable results with greater precision and power.…”
Section: Discussionmentioning
confidence: 99%